Sexual orientation-related disparities in perinatal mental health among a prospective cohort study - Kodiak R.S. Soled; Sarah McKetta; Payal Chakraborty; Colleen A. Reynolds; S. Bryn Austin; Jorge E. Chavarro; A. Heather Eliassen; Siwen Wang; Sebastien Haneuse; Brittany M. Charlton (Elsevier, 2024)
Sexually minoritized women (SMW) may be at an increased risk of adverse perinatal mental health, though prior research is limited. We examined sexual orientation-related differences in perinatal mental health (i.e., stress and depression), and antidepressant utilization among those at different severities of clinically significant perinatal depressive symptoms.Nurses' Health Study 3 participants with prospectively assessed pregnancies (N = 6,364) received pregnancy and postpartum questionnaires. Using weighted log-binomial generalized estimating equations, we examined differences in stress (Perceived Stress Scale 4 [PSS-4]), depression (the Edinburgh Postnatal Depression Scale [EDPS] at four cut-off scores [≥7, ≥9, ≥11, ≥13]), and patterns of antidepressant utilization across five groups: completely heterosexual with no same-sex sexual partners (reference group; n = 5,178); heterosexual with same-sex sexual partners (n = 245); mostly heterosexual (n = 770); bisexual (n = 106); and lesbian (n = 47).Compared to the completely heterosexual reference group, SMW reported increased stress during pregnancy (adjusted risk ratio [ARR]: 1.14, 95% confidence interval [1.02-1.28]). SMW reported an elevated risk of pregnancy depression at every EDPS score cutoff, with the magnitude of the disparity increasing as the score increased (ARRs: 1.09 [1.00-1.20]; 1.20 [1.05-1.36]; 1.37 [1.16-1.63]; 1.49 [1.18-1.89] for EDPS scores ≥7, ≥9, ≥11, ≥13, respectively). Disparities were highest in magnitude among the mostly heterosexual and bisexual subgroups. Utilization of postpartum antidepressants increased among the reference group with increasing symptom severity but was only associated at the highest score (≥13) among SMW subgroups.SMW have increased risks of pregnancy stress and depression and are more likely to use perinatal antidepressants; mostly heterosexual and bisexual individuals had the highest risk of antidepressant use. Postpartum symptom severity closely corresponded to antidepressant use among completely heterosexual, but not SMW-suggesting disparities in mental health treatment. Further research priorities include determining the causes of these disparities and appropriately tailored solutions.